2016
DOI: 10.1063/1.4941151
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of bacterial cellulose nanocrystalline from pineapple peel waste: Optimization of acid concentration in the hydrolysis method

Abstract: Abstract. Isolation of needle-shaped bacterial cellulose nanocrystalline with a diameter of 16-64 nm, a fiber length of 258-806 nm, and a degree of crystallinity of 64% from pineapple peel waste using an acid hydrolysis process was investigated. Experimental showed that selective concentration of acid played important roles in isolating the bacterial cellulose nanocrystalline from the cellulose source. To achieve the successful isolation of bacterial cellulose nanocrystalline, various acid concentrations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In addition, there is the possibility of producing CNSs from a multitude of sustainable, widely available and lowcost resources such as forest residues (wood saw-dust -pine and eucalyptus), agricultural (wheat straw, sugar cane) and industrial (cotton waste, paper waste, and tobacco industry) [2,[8][9][10][11][12]. CNSs can be applied in a variety of areas, such as electronic displays, paints, packaging, membranes, implants, polymer composites and others [13]. The application is highly dependent on the nanocellulose properties and its surface chemistry [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is the possibility of producing CNSs from a multitude of sustainable, widely available and lowcost resources such as forest residues (wood saw-dust -pine and eucalyptus), agricultural (wheat straw, sugar cane) and industrial (cotton waste, paper waste, and tobacco industry) [2,[8][9][10][11][12]. CNSs can be applied in a variety of areas, such as electronic displays, paints, packaging, membranes, implants, polymer composites and others [13]. The application is highly dependent on the nanocellulose properties and its surface chemistry [14].…”
Section: Introductionmentioning
confidence: 99%
“…The lowest BC production by K. rhaeticus K23 was recorded at 26 • C and the maximum production was obtained at 32 • C (Figure 3). Many researchers have found that the optimum growth temperature for biocellulose production is 30 • C [38][39][40][41]. However, this may be due to the strains which they used in their studies (Acetobacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of consistency in nomenclature has cost plenty of efforts to search, understand, and cross-check different materials. The terms that have been used include cellulose nanocrystal [25], cellulose nano-crystal [26], cellulose nanocrystalline [27], crystalline cellulose nanofibril [28], nano-fiber [29] nano-cellulose [30] nanocrystalline cellulose [31], cellulose nanofibril [20], nanofibrillated cellulose [6], nanofibrillar cellulose [32], nano-fibrillated cellulose [33], cellulose nanofiber [34]. The subjective use of different terms for the same material may lead to confusion, misunderstanding, and miscommunication in this domain area, Cao -eXPRESS Polymer Letters Vol.12, No.9 (2018) and therefore it is crucial to standardize the terminology.…”
Section: Y Caomentioning
confidence: 99%